1.3 and 1.55μm Thermally Regenerated Gratings in Hydrogenated Boron/Germanium Co-Doped Photosensitivity Fiber - Yang, H.Z.; Chong, W.Y.; Qiao, X.G.; Lim, M.J.; Lim, K.S.; Islam, M.R.; Ali, N.M.; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2013)
In this paper, we have experimentally demonstrated thermal regeneration of gratings at 1310 and 1560 nm in the hydrogenated boron/germanium codoped photosensitivity fibers. Increase in effective index of the fiber and reduced grating period are observed in the regenerated fiber Bragg grating (RFBG). The experimental results show that the temperature sensitivity of regenerated gratings at 1310 and 1560 nm is 8.7 and 12.8 pm/ °C, respectively, and the RFBG with larger period withstand a higher thermal stability.